Abordagens de ensino das classes de palavras invariáveis em livros didáticos de língua portuguesa entre 1999-2020 - Sousa, Francisco Rafael Mota de (2021)
A spontaneous observation of the educational process allows us to recognize that the textbook, by registering and spreading cultural practices of a certain community, constitutes a rich tool that helps us to understand not only how pedagogical processes are developed, but also reflects the political, social and economic aspirations of a time and society. From this perspective, we believe that about the teaching of grammar in the Portuguese class, the textbook has followed the language teaching practices throughout the years and today reflects the discussions about a pedagogy of grammatical knowledge, as well as the different teaching approaches in the school treatment of the linguistic phenomenon. Given the prominent place that grammar has always assumed in the Portuguese class and in the textbook, the present work aims to investigate the approaches to teaching the classes of invariable words in Portuguese textbook exercises for the final years of elementary school published between 1999 and 2020. For this enterprise, based on Halliday, McIntosh and Strevens (1974), Bloom et al. (1972) and the prescriptions of official documents that guide language teaching in Brazil, such as the PCN and the BNCC, we seek not only to describe the teaching approaches present in textbooks, but also to verify the recommendations of the official documents for the teaching of word classes and, with this, analyze how the movements of conservation and change occur in the development of such approaches. From the method's point of view and starting from a documentary research, we investigated eight collections of Portuguese language textbooks destined to the final years of elementary school, approved in the PNLD, and analyzed the text of the PCN and BNCC. The research proved that there is in the textbooks a treatment given to the invariable word classes through two approaches: a descriptive one and a productive one, being the most predominant one, contradicting the official discourse of the PCN and the BNCC that the teaching of the word classes should be developed from an essentially productive approach in the use of language. The analysis of the collections through the defined cutout also confirmed the coexistence of descriptive and productive approaches to language teaching in the Portuguese language textbook, demonstrating that the teaching material tries to balance conservative and innovative postures with regard to grammar teaching, which configures a slow change in the effectiveness of language teaching that values the expansion of effective language use skills in different social contexts.